Six Ways Population Change Will Affect the Global Economy - Mason, Andrew J. (2022)
New estimates of economic flows by age combined with population projections show that in the coming decades (1) global GDP growth could be slower by about 1 percentage point per year, declining more sharply than population growth; (2) GDP will shift toward sub-Saharan Africa more than population trends suggest; (3) living standards of working-age adults may be squeezed by high spending on children and seniors; (4) changing population age distribution will raise living standards in many lower-income nations; (5) changing economic life cycles will amplify the economic effects of population aging in many higher income economies; and (6) population aging will likely push public debt, private assets, and perhaps productivity higher. Population change will have profound implications for national, regional, and global economies.